A Review of Resistive Switching Devices: Performance Improvement, Characterization, and Applications. Issue 4 (24th February 2021) - Shi, Tuo; Wang, Rui; Wu, Zuheng; Sun, Yize; An, Junjie; Liu, Qi
Abstract : As human society enters the big data era, huge data storage and energy‐efficient data processing are in great demand. The resistive switching device is an emerging device with both inherent memory and computation capabilities. It may bring disruptive influences to modern information technology from bottom up. After decades of study of the materials, mechanisms, and devices, the maturity of the resistive switching device in various applications, for example, nonvolatile memory, artificial neural networks, and information security, could be foreseen. Herein, the recent progress of the resistive switching device from the aspects of materials, devices, and applications is reviewed. First, the resistive switching device, including mechanisms and materials, is briefly discussed. Performance improvement methods with respect to individual device properties are systematically illustrated. Second, characterization technologies for understanding the mechanism and guidance of device design are classified and discussed in depth. Third, various applications based on resistive switching devices are summarized. The review ends with a brief conclusion concerning the challenges from mechanism to algorithm level and the future outlook. Abstract : The resistive switching device is an emerging device with simple structure, ease of 3D integration, low power consumption, high speed, and good scalability. It has capabilities of data storage and computation due to its intrinsic physical mechanism. Therefore, the resistive switching device can not only be used for memory, but also for computation and security applications.